Who shapes carbon neutrality? A comparative study of industry and non-industry coalitions via social network analysis - Seo, Inseok; Lee, Youhyun (International Review of Public Administration, 2025)
South Korea implemented a new act to legalize carbon neutrality to combat the climate crisis targets by 2050. However, there were conflicts among different policy coalitions in setting the direction of the carbon neutral policy. This study explored the reactions of South Korean industry and non-industry policy coalitions to carbon neutrality initiatives, including the global carbon neutral paradigm and the Carbon Border Adjustment Mechanism (CBAM). This study utilizes the advocacy coalition framework (ACF) to explain policy coalitions. ACF’s belief system explains how industry and non-industry policy coalitions are structured and persist. This study conducted an expert survey but diversified the response analysis using social network analysis and the pairwise comparison method. Awareness of and preparation for the CBAM was important to the industry coalition, whereas the non-industry coalition focused on institutional processes and greenhouse gas mitigation and was more interested in the democratic process of policymaking.
Keywords: Advocacy Coalition Framework; carbon neutrality; climate crisis; coalition; social network analysis